Optimal Layout and Overheat Monitoring for Components of Highly Reliable Relay Protection Equipment - Long Jin; Zexin Zhou; Rongrong Zhan; Guosheng Yang; Yongdong Zhang (IEEE Access, 2023)
Effective thermal management measures are of great significance for improving the reliability of relay protection equipment. Firstly, the paper establishes a temperature calculation function for components based on the thermal superposition model, calculates the minimum heat dissipation distance between components, and converts the functional coordination of components into coordinate constraints. An optimised layout scheme for components is obtained quickly based on the minimum heat dissipation distance and coordinate constraints. The finite element simulation results show that the optimized layout significantly improves the temperature of the components, with a maximum temperature reduction of 8.6%. Then a component overheating warning strategy is proposed based on state recognition. The life-accelerated decay ratio of the components is calculated by monitoring the operating temperature, and the allowable operating time and alarm signal of the components at a specific temperature are combined to reflect the components’ status accurately.